Gambaran Kadar Pepsin pada Saliva Pasien Refluks Laringofaring di RSUP Dr. M. Djamil Padang - Mutiara Adinda Rahma; Ade Asyari; Yustini Alioes (Fakultas Kedokteran Universitas Andalas, 2023)
Laryngopharyngeal reflux (RFL) is a condition of tissue inflammation in the upper aerodigestive tract due to the reflux of gastric and duodenal contents, the symptoms such as post-nasal drip, globus sensation, and heartburn which decrease quality of life. RFL was diagnosed subjectively using the Reflux Symptom Index (RSI) and Reflux Finding Score (RFS). The pepsin levels in saliva that were detected by ELISA can be a sensitive and objective diagnostic marker for RFL because pepsin was only produced by chief cells in the stomach. The purpose of this study was to determine the characteristics of RFL patients based on age, sex, features of complaints in RSI, features of anatomic abnormalities in RFS, and salivary pepsin levels. This study was a descriptive observational retrospective design. From September to October 2022, this study was carried out at the Medical Record Department of RSUP Dr. M. Djamil Padang. The Lemeshow formula was used as the minimum number sampling in this study, 22% was the value of the proportion of events. The findings of this study revealed that 20 patients with RFL were tested for pepsin levels in saliva at Dr. RSUP. M. Djamil Padang, with nearly the same total number of RFL patients in each age group. The majority of RFL patients (60.0%) were female, and the most common complaint felt by RFL sufferers was post-nasal drip (90.00%). The most common anatomic abnormality was diffuse laryngeal edema (100%), and the mean pepsin levels in saliva was 15.863 ng/mL. Pepsin was found in all samples. Keywords: laringofaringeal reflux, pepsin, saliva